QoS-satisfied dynamic routing based on overlay service network - Amir Karamoozian, 1985-, author; Mostafa Erfani, 1984-, author; Abdul Hanan Abdullah, author; International Conference on Communication Software and Networks (2010 : Singapore) (Skudai : Universiti Teknologi Malaysia, 2010)
PRZSL